Efficacy and Safety of Rovalpituzumab Tesirine in Third-Line and Beyond Patients with DLL3-Expressing, Relapsed/Refractory Small-Cell Lung Cancer: Results From the Phase II TRINITY Study - Morgensztern, Daniel (Clin Cancer Res, 2019)
PURPOSE: Although extensive-stage small-cell lung cancer (SCLC) is highly responsive to first-line therapy, virtually all patients develop resistance with short survival. Rovalpituzumab tesirine (Rova-T) is an antibody–drug conjugate targeting delta-like 3 protein (DLL3). This open-label, single-arm, phase II study (TRINITY) assessed safety and efficacy of Rova-T in patients with DLL3-expressing SCLC in the third-line and beyond (3L+) setting. PATIENTS AND METHODS: Patients with DLL3-expressing SCLC (determined by mouse antibody immunohistochemistry [IHC] assay), and ≥2 prior regimens, received 0.3 mg/kg Rova-T once every 6 weeks for two cycles. During study, a rabbit antibody IHC assay was developed and used for the final analysis, with DLL3-positive and DLL3-high defined as ≥25% and ≥75% of tumor cells positive for DLL3, respectively. The primary end points were objective response rate (ORR) and overall survival (OS). RESULTS: Among 339 patients enrolled, 261 (77%) had two prior lines of therapy and 78 (23%) had ≥3. DLL3-high and DLL3-positive tumors by rabbit IHC were seen in 238 (70%) and 287 (85%) patients, respectively. The remaining 52 (15%) were DLL3-negative only by rabbit IHC or had missing results. ORR was 12.4%, 14.3%, and 13.2% in all, DLL3-high, and DLL3-positive patients, respectively. Median OS was 5.6 months in all patients and 5.7 months in DLL3-high patients. The most common adverse events (AE) were fatigue, photosensitivity reaction, and pleural effusion. Grade 3–5 AEs were seen in 213 (63%) patients. CONCLUSIONS: Rova-T is the first targeted agent in SCLC to use DLL3, a novel biomarker. However, results demonstrate modest clinical activity in 3L+ SCLC, with associated toxicities.